Doing educational research in Chinese societies: Hong Kong SAR & China. Issue 3 (8th July 2019) - Zhang, Yi-Hai; Peng, Hongyu; Cheung, Hin Wah Chris; Chong, King Man Eric; Chow, Chin Fung Philip
Abstract : Purpose: The purpose of this paper is to explore the differences between Hong Kong Special Administrative Region (SAR) and Mainland in terms of education and also the influence of it on doing comparative educational research. Hong Kong SAR is ruled by the Chinese Government under the framework of "One country, two systems." It makes Hong Kong SAR different from other Mainland cities based on different aspects including, education. The finding of this paper provides a systematic review about the differences between these two Chinese societies in terms of education and also implication for conducting comparative educational research in these two societies and also generating some implications for cross-national and cross-cultural study in education. Design/methodology/approach: This paper made references from the framework proposed by Bray and Thomas (1995) in relation to comparative educational research to make comparison between Hong Kong SAR and Mainland China. Multi-level comparison is conducted between two societies in terms of education, especially aspects relating to conducting educational research sat social, school and individual levels. Findings: This paper identified the influence of "One county, two systems" on education at different levels such as ideology, school management system and use of languages in teaching. Such differences affect the choice of topics, sampling strategy, research design, data analysis and interpretation and also ethical considerations when conducting comparative research between Hong Kong SAR and Mainland China. Originality/value: This paper is an integrated analysis of conducting educational research in two Chinese societies and provides insights for further discussions and possible research about this topic.